Pemilihan Legislatif Kabupaten Pesawaran 2024: Analisis Strategi Pemenangan Atut Widiarti Oleh DPD Partai Keadilan Sejahtera - M. Adiatma Widada Widada; Abdul Qohar; Angga Natalia (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The dynamics of local politics in Indonesia often present an interesting phenomenon in the form of a candidate's success in maintaining their seat during several election periods, this phenomenon is relevant to be studied more deeply. This study aims to analyze the winning strategy of Atut Widiarti as a legislative candidate for the Partai Keadilan Sejahtera in the 2024 Pesawaran Regency Regional People's Representative Council election. The focus of the research is directed at the Partai Keadilan Sejahtera efforts through its organizational structure and cadre network to formulate and implement political strategies to gain public support. The research method used in this study is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the winning strategy was implemented through a combination of political marketing theories from Adman Nursal which include indicators of push marketing, pull marketing, and pass marketing theories. This study concludes that Atut Widiarti's success in winning a seat in the Pesawaran Regency Regional Representative Council for the 2024-2029 period was influenced not only by the strength of the candidate's figure, but also by the Partai Keadilan Sejahtera consistency in building political communication that is adaptive to the needs of the local community. These findings are expected to contribute to the study of political science, particularly in understanding the dynamics of winning strategies at the regional election level. Keywords: Winning Strategy, Legislature, Prosperous Justice Party